Project Based Learning (PjBL) Model with STEAM Approach: Its Impact on Students Creative Thinking Skills on Energy in Living System Topic - Permana, Niki Dian; Lestari, Ina; Susanty Harahap, Fatimah Depi; Azhar, Azhar; Defianti, Aprina (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This research aims to determine the increase in creative thinking skills of secondary school students through the application of the PjBL model with a STEAM approach to energy materials in living systems. This research uses a true experimental method with a pretest-posttest control group design. The population of this study was all class VII students. The sample selection used a simple random sampling technique so that one experimental class was selected which applied the PjBL model with the STEAM approach and one control class which applied the conventional learning model. Data collection was carried out through creative thinking skills test questions and observation sheets. Posttest data on students' creative thinking skills were analyzed using the Mann-Whitney test, and observation sheets were analyzed using descriptive analysis. The results of the analysis using the N-gain test in the control class obtained a value of 47,4 in the medium category and the experimental class with an N-gain of 71 in the high category. It can be concluded that there is a significant increase in students' creative thinking skilss after learning using the PjBL model with the STEAM approach in learning Energy in Living Systems.Keywords: project based learning, steam, creative thinking skills, energy in living systems